A population of murine hematopoietic progenitors expresses an endogenous retroviral gp70 linked to the Rmcf gene and associated with resistance to erythroleukemia - Buller, RS (The Rockefeller University Press, 1989)
Multiple copies of retroviral sequences are stably integrated in the genomes of many higher organisms, and are thus transmitted vertically to offspring via the germline (1). Most of these heritable viral genes are not expressed, and expression, when observed, is commonly limited to envelope (env) genes as demonstrated by the presence of cell surface and serum envelope glycoprotein (gp70) in mice. Studies of the mouse have shown that certain tissues such as the reproductive tract and lymphoid organs are common sites for the expression of endogenous env genes, suggesting that the transcription of at least some endogenous sequences is tissue specific. The transcription of endogenous viral genes is regulated by both cis and trans mechanisms (2-5) and their expression can be temporally linked to differentiation and development (6-8). The consequences to the host of endogenous retroviral genes are varied. At one extreme, expression of endogenous virus can result in the development of leukemia and death. Another potentially detrimental effect is that of insertional mutagenesis, seen when the integration of retroviral sequences interrupts the functioning of a cellular gene (9, 10). However, it is now clear that expression of endogenous retroviral genes may also have a beneficial effect for the host: namely, mediating resistance to retroviral leukemias as has been demonstrated for the Fv-4 gene in mice (11) and some ea loci in chickens (12). This form of resistance is due to the blockage of cellular viral receptors by the expression of envelope glycoprotein on the cell surface. The Rmcf locus of the mouse is another resistance gene that may exert its effect by the expression of an endogenous env gene. A summary of our current state of knowledge concerning the Rmcf gene is shown in Table I. The Rmcf gene was originally described when it was observed that fibroblast cell cultures derived from certain strains of mice restricted the replication of recombinant mink cell focus-forming(MCF)1 viruses (13). As detailed in Table I, DBA/2 mice are the prototypic strain exhibiting the Rmcf resistance (Rmcf(r)) phenotype. Cell cultures from other strains, such as C57BL/6 and IRW, are permissive for MCF viral replication and are termed Rmcf sensitive (Rmcf(s)). Previously, we described two allelic forms of an endogenous env gene, whose expression is linked to the Rmcf gene (14). Cell cultures from Rmcf(r) mice express gp70 related to that of MCF viruses, whereas cultures derived from Rmcf(s) mice either express no gp70 (IRW) or express an endogenous xenotropic gp70 (C57BL/6). These two gp70 alleles are detectable by type-specific mAbs.